Report on industrial attachment with Institute of Molecular and Cell Biology (IMCB). - Chen, Siying. (2009)
Alzheimer’s disease (AD) is the most common form of dementia, inflicting millions of people worldwide, notably the elderly. It is a degenerative and fatal brain disorder, for which there is still no cure. Even though amyloid plaques and neurofibrillary tangles are believed to be related to the onset and the progression of the disease, the mechanisms still remain unclear. Patients suffering from AD usually display loss of memory as one of the earliest symptoms. This is because the hippocampus region, which is responsible for spatial memory, is one of the first brain regions to be affected by the disease. In order to understand how the disease progresses and how it affects the hippocampus in the brain, it is essential to know the mechanism behind memory formation and retention. This project investigates the role of wip1 protein in spatial memory formation and retention and attempts to draw out the relationship between different hippocampus neuronal proteins. Two types of in vivo behavioural studies investigate the phenotypic impact of wip1 protein on the wip1 wild type and knock out mice. On the other hand, in vitro studies like immunostaining and dendrite morphology investigation give insight into how wip1 affects the cells and tissues.